2013
DOI: 10.1002/ccd.25277
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing rotational atherectomy in high‐risk percutaneous coronary interventions: Insights from the PROTECT ΙΙ study

Abstract: Patients who were treated with RA had more comorbidities, and more complex and extensive coronary artery disease. In patients with Impella, more aggressive RA use resulted in fewer revascularization events but higher incidence of periprocedural MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 29 publications
0
29
0
Order By: Relevance
“…Furthermore, the use of circulatory support devices, such as intra-aortic balloon pump or Impella (Abiomed Inc, Danvers, MA), may reduce the incidence of severe complications even in high-risk RA patients, such as those with left main disease or left ventricular dysfunction. 22 In institutional class, the rate of the composite outcomes in high-volume institutions was approximately half of that in low-volume institutions. As Badheka et al 23 reported that an increase in operator and institutional volume of PCI was associated with a decrease in adverse outcomes, institutional volume of RA should be the important factor for the occurrence of adverse events.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the use of circulatory support devices, such as intra-aortic balloon pump or Impella (Abiomed Inc, Danvers, MA), may reduce the incidence of severe complications even in high-risk RA patients, such as those with left main disease or left ventricular dysfunction. 22 In institutional class, the rate of the composite outcomes in high-volume institutions was approximately half of that in low-volume institutions. As Badheka et al 23 reported that an increase in operator and institutional volume of PCI was associated with a decrease in adverse outcomes, institutional volume of RA should be the important factor for the occurrence of adverse events.…”
Section: Discussionmentioning
confidence: 97%
“…The potential mechanism for late benefit may relate to more stable procedural hemodynamics allowing for greater and more complete revascularization, including allowing for more complex PCI procedures such as rotational atherectomy. 97 No comparable randomized trial of HR-PCI with the TandemHeart device exists. Alli et al reported a series of 54 patients using the TandemHeart for HR-PCI.…”
Section: Percutaneous Mechanical Circulatory Supportmentioning
confidence: 99%
“…Interestingly, this is consistent with the late mortality reduction demonstrated in BCIS-1 and has been the cause of intense speculation. The potential mechanism for late benefit may relate to more stable procedural hemodynamics allowing for greater and more complete revascularization, including allowing for more complex PCI procedures such as rotational atherectomy [97].…”
Section: Percutaneous Mechanical Circulatory Supportmentioning
confidence: 99%